IL-1β-MyD88-mTOR Axis Promotes Immune-Protective IL-17A+Foxp3+ Cells During Mucosal Infection and Is Dysregulated With Aging - Bhaskaran, Natarajan; Faddoul, Fady; Paes da Silva, Andre; Jayaraman, Sangeetha; Schneider, Elizabeth; Mamileti, Prerna; Weinberg, Aaron; Pandiyan, Pushpa (Frontiers in Immunology, 2020)
CD4+Foxp3+Tregs maintain immune homeostasis, but distinct mechanisms underlying their functional heterogeneity during infections are driven by specific cytokine milieu. Here we show that MyD88 deletion in Foxp3+ cells altered their function and resulted in increased fungal burden and immunopathology during oral Candida albicans (CA) challenge. Excessive inflammation due to the absence of MyD88 in Tregs coincided with a reduction of the unique population of IL-17A expressing Foxp3+ cells (Treg17) and an increase in dysfunctional IFN-γ+/Foxp3+ cells (TregIFN-γ) in infected mice. Failure of MyD88-/- Tregs to regulate effector CD4+ T cell functions correlated with heightened levels of IFN-γ in CD4+ T cells, as well as increased infiltration of inflammatory monocytes and neutrophils in oral mucosa in vivo. Mechanistically, IL-1β/MyD88 signaling was required for the activation of IRAK-4, Akt, and mTOR, which led to the induction and proliferation of Treg17 cells. In the absence of IL-1 receptor signaling, Treg17 cells were reduced, but IL-6-driven expansion of TregIFN-γ cells was increased. This mechanism was physiologically relevant during Candida infection in aged mice, as they exhibited IL-1 receptor/MyD88 defect in Foxp3+ cells, loss of p-mTORhighTreg17 cells and reduced levels of IL-1β in oral mucosa, which coincided with persistent tongue inflammation. Concurrent with Treg dysfunction, aging was associated with increased CD4+ T cell hyperactivation and heightened levels of IL-6 in mice and humans in oral mucosa in vivo. Taken together, our data identify IL-1β/MyD88/Treg axis as a new component that modulates inflammatory responses in oral mucosa. Also, dysregulation of this axis in an aging immune system may skew host defense towards an immunopathological response in mucosal compartments.